Voting on Urban Land Development - Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper, we analyze several local referendums on land development and land-use regulation in the City of Erlangen (Germany) in the period between 2011 and 2018. To identify the positive influence of the travel distance on approval for the development of land, we employ a two-way fixed-effects model and use spatial instruments. Also, we analyze the heterogeneity of city dwellers' preferences for the development of residential and commercial areas. In particular, we examine the homeownership and expenditure-crowding-out hypotheses.
Keywords: D72; R52; R58; 330; land development; referendum; local public goods; distance decay; homeownership; expenditure-crowding out